2017
DOI: 10.1152/ajprenal.00688.2016
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium improves cisplatin-mediated tumor killing while protecting against cisplatin-induced nephrotoxicity

Abstract: Approximately 30% of all cancer patients treated with cisplatin, a widely used broad-spectrum chemotherapeutic agent, experience acute kidney injury (AKI). Almost all patients receiving cisplatin have magnesium (Mg) losses, which are proposed to aggravate AKI. Currently, there are no methods to successfully treat or prevent cisplatin-AKI. Whereas Mg supplementation has been shown to reduce AKI in experimental models and several small clinical trials, the effects of Mg status on tumor outcomes in immunocompeten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Hypomagnesemia and inhibition of renal magnesium uptake are observed to have an additive effect on cisplatininduced renal toxicity in animal models, whereas magnesium infusion significantly reduces renal cisplatin accumulation and cisplatin-induced nephrotoxicity in a dose-dependent manner [14,15]. In a study of mice bearing colon tumors, magnesium supplementation was shown to protect against cisplatin cytotoxicity without compromising cisplatin's antitumor efficacy in vivo [16]. Our study adds critical clinical evidence that appeals for research effort to study the impact of magnesium supplementation on survival in patients with ovarian cancer receiving platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia and inhibition of renal magnesium uptake are observed to have an additive effect on cisplatininduced renal toxicity in animal models, whereas magnesium infusion significantly reduces renal cisplatin accumulation and cisplatin-induced nephrotoxicity in a dose-dependent manner [14,15]. In a study of mice bearing colon tumors, magnesium supplementation was shown to protect against cisplatin cytotoxicity without compromising cisplatin's antitumor efficacy in vivo [16]. Our study adds critical clinical evidence that appeals for research effort to study the impact of magnesium supplementation on survival in patients with ovarian cancer receiving platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…66 , and preclinical studies have shown a protective effect of normal SMg levels in models of cisplatininduced nephrotoxicity. [67][68][69]…”
Section: Platinum-based Chemotherapymentioning
confidence: 99%
“…Cisplatin decreases serum magnesium [26]. Magnesium deficiency increases AKI severity [27] by decreasing expression of efflux transporters and allowing for cisplatin accumulation in tubular cells [28,29]. Kumar et al recently showed that magnesium supplementation protected against AKI and did not interfere with the anti-tumour effects of cisplatin [27].…”
Section: Introductionmentioning
confidence: 99%